2021
DOI: 10.1371/journal.pcbi.1009105
|View full text |Cite
|
Sign up to set email alerts
|

Pathway analysis in metabolomics: Recommendations for the use of over-representation analysis

Abstract: Over-representation analysis (ORA) is one of the commonest pathway analysis approaches used for the functional interpretation of metabolomics datasets. Despite the widespread use of ORA in metabolomics, the community lacks guidelines detailing its best-practice use. Many factors have a pronounced impact on the results, but to date their effects have received little systematic attention. Using five publicly available datasets, we demonstrated that changes in parameters such as the background set, differential m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 57 publications
0
66
0
Order By: Relevance
“…A powerful method to describe peculiar features of the cell metabolism is pathway analysis (PA), which provides a graphical representation of the relationships among the actors (mainly enzymes and metabolites) of precise catalyzed reactions. Therefore, PA is highly employed for the interpretation of high-dimensional molecular data [74]. In fact, taking advantage of the already acquired knowledge of biological pathways, proteins, metabolites and also genes can be mapped onto newly developed pathways with the objective to draw their collective functions and interactions in that specific biological environment [75].…”
Section: Pathway Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A powerful method to describe peculiar features of the cell metabolism is pathway analysis (PA), which provides a graphical representation of the relationships among the actors (mainly enzymes and metabolites) of precise catalyzed reactions. Therefore, PA is highly employed for the interpretation of high-dimensional molecular data [74]. In fact, taking advantage of the already acquired knowledge of biological pathways, proteins, metabolites and also genes can be mapped onto newly developed pathways with the objective to draw their collective functions and interactions in that specific biological environment [75].…”
Section: Pathway Analysis Methodsmentioning
confidence: 99%
“…Three are the necessary inputs in ORA analysis: (i) a set of pathways (or metabolite collections); (ii) a catalog of investigating metabolites and, (iii) a background collection of compounds. The list of investigating metabolites usually comes from experimental data after applying a statistical test to determine those metabolites whose signals can be associated with a precise result by choosing a threshold value usually associated to the p-values [74]. The background collection includes all metabolites that can be revealed in the considered measurement.…”
Section: Over-representation Analysis (Ora)mentioning
confidence: 99%
“…Furthermore, the authors argued that the choice of gene set collections should not be made arbitrarily as certain gene sets may be more or less suitable for a particular dataset than others. In a recent study on best practices for the popular ORA method on metabolomics data [ 65 ], the authors also found that the results of pathway analysis substantially differed based on the choice of pathway database (i.e. KEGG, Reactome and BioCyc [ 66 ]).…”
Section: Impact Of Pathway Database and Gene Set Sizementioning
confidence: 99%
“…Details on various possibilities of handling NMR-based metabolomics data can be consulted elsewhere ( Blaise et al, 2021 ; Debik et al, 2022 ). Beyond statistical treatment, web-based tools like MetaboAnalyst ( Chong et al, 2018 ) allow to visualise metabolomics data in an user-friendly way, and are able to perform additional tasks, as for example pathway enrichment analysis ( Wieder et al, 2021 ).…”
Section: Computational Tools and Resourcesmentioning
confidence: 99%